Distributed systems : principles and paradigms - Tanenbaum, Andrew S., 1944-; Van Steen, Maarten, ....- (Upper Saddle River, NJ : Pearson Prentice Hall, 2007)
Virtually every computing system today is part of a distributed system. Programmers, developers, and engineers need to understand the underlying principles and paradigms as well as the real-world application of those principles. Now, internationally renowned expert Andrew S. Tanenbaum - with colleague Martin van Steen - presents a complete introduction that identifies the seven key principles of distributed systems, with extensive examples of each. Adds a completely new chapter on architecture to address the principle of organizing distributed systems. Provides extensive new material on peer-to-peer systems, grid computing and Web services, virtualization, and application-level multicasting. Updates material on clock synchronization, data-centric consistency, object-based distributed systems, and file systems and Web systems coordination. For all developers, software engineers, and architects who need an in-depth understanding of distributed systems.
Includes bibliographical references (p. 623-668) and index.
Keywords: Distributed operating systems (Computers).; Electronic data processing -- Distributed processing; Gedistribueerde computersystemen; Operating systems